Antioxidant compounds of Iranian olive oils influenced by growing area, ripening stage, and cultivar. Issue 1 (7th June 2016) - Noorali, Mehry; Barzegar, Mohsen; Sahari, Mohammad Ali
Abstract : Phenolic and tocopherol compounds of virgin olive oils, obtained from three imported cultivars (cvs) of Mission, Beleydi, and Koroneiki collected in two different ripening stages from two completely different regions (subdesertic zone (Qom) and Caspian zone (Gorgan)), were determined. Regardless of the growing area conditions, Beleydi cultivars showed the lowest oil content, total phenolic content, secoiridoids, and oleuropein aglycone along with the highest content of decarboxy methyl ligstroside aglycon, ligstroside aglycone, and consequently the lower oxidative stability. Moreover, in spite of lower oil contents, the cvs growing in Qom had higher total phenolic compounds, secoiridoids, oleuropein aglycone and higher oxidative stability. Furthermore, the amount of most of the studied components decreased during the ripening stages. Practical applications: For selection of well‐characterized cvs, assessing cv‐cultivation zone‐maturity seems unavoidable before commercialization. This trend supports the differentiation of various olive oils and have motivated new and unique branding that assist their sales as well as the need for evaluating the adaptability of imported olive cvs into different growing areas and the most appropriate time of harvest before developing plantations, as a key point for mills due to the increased competitiveness and quality protection. Physicochemical properties of selected olive cultivars grown in Iran were determined and a correlation between their phenolic compounds and oxidative stability was achieved. Finally, geographic origin of olive cvs was determined by using principal component analysis. Abstract : Physicochemical properties of selected olive cultivars grown in Iran were determined and a correlation between their phenolic compounds and oxidative stability was achieved. Finally, geographic origin of olive cvs was determined by using principal component analysis.